2019
DOI: 10.1111/bph.14565
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of α‐adrenoceptor signalling protects photoreceptors after retinal detachment by inhibiting oxidative stress and inflammation

Abstract: Background and Purpose Currently available treatments do not halt progression of photoreceptor death and subsequent visual impairment related to retinal detachment (RD) which is observed in various retinal disorders. This study investigated the neuroprotective effects of two adrenoceptor ligands, the α1‐adrenoceptor antagonist doxazosin and the α2‐adrenoceptor agonist guanabenz, against photoreceptor cell death in RD. Experimental Approach We used a model of experimental RD in Brown‐Norway rats induced by subr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Recent studies have shown that RIP kinase-mediated necrotic signaling [ 69 ] and FAS-mediated apoptosis pathway [ 70 ] contribute to photoreceptor death after RD. However, accumulating evidence suggests that the rapid increase of oxidative stress is currently considered to be a critical event for irreversible cellular damage in RD [ 14 ]. Previous studies have demonstrated an increased generation of ROS after RD, whereas photoreceptor cell death can be prevented after RD by suppressing ROS [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that RIP kinase-mediated necrotic signaling [ 69 ] and FAS-mediated apoptosis pathway [ 70 ] contribute to photoreceptor death after RD. However, accumulating evidence suggests that the rapid increase of oxidative stress is currently considered to be a critical event for irreversible cellular damage in RD [ 14 ]. Previous studies have demonstrated an increased generation of ROS after RD, whereas photoreceptor cell death can be prevented after RD by suppressing ROS [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent with this, previous studies have demonstrated that microglia A 2A R blockade suppresses elevated pressure-induced oxidative stress in retina [ 32 ]. Furthermore, modulation of α -adrenoceptor signaling protects photoreceptors from apoptosis after RD by inhibiting ROS production [ 14 ]. In our work, we showed that ZM241385 was able to prevent photoreceptor loss from ROS overproduction triggered after RD, further reinforcing its role in controlling retinal neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Murakami et al [86] conducted a study on photoreceptor cell death and RD, and considered that a better understanding of the molecular mechanisms related to the death of these cells would allow new therapies to be developed to prevent vision deficits due to loss of photoreceptor cells. According to Li et al [87], currently, no effective therapy is clinically available to protect photoreceptor cells. Therefore, the development of neuroprotective reagents for photoreceptors could contribute to long-term visual stability for postoperative RD patients.…”
Section: Retinal Detachmentmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are mainly derived from the respiration of mitochondria [25]. Recent studies in the ophthalmology field found that photoreceptors were the main source of ROS production in an experimental RD rat model [26] and that excess ROS led to photoreceptor cell death [11]. Coincidentally, TRPML1 was demonstrated to remove excess ROS and ROS accumulated in both a TRPML1 knockdown (KD) cell line and a skin fibroblast cell line from an MLIV patient [21, 27].…”
Section: Introductionmentioning
confidence: 99%